EFEKTIFITAS PEMBERIAN SEDUHAN JAHE DAN DAUN MINT DALAM MENGURANGI FREKUENSI MUAL MUNTAH PADA IBU HAMIL TRIMESTER PERTAMA - sumarni Marwang; Jumrah; Rosita (Poltekkes Kemenkes Medan, 2022)
Nausea and vomiting (Morning Sickness) in pregnant women due to increased levels of the hormones Estrogen, Progesterone and Human Chorionic Gonadotropine (HCG) in serum from the placenta. Continuous nausea and vomiting will have an impact on the health conditions of the mother and fetus. Ginger and mint leaves are one way to reduce nausea and vomiting during pregnancy. The purpose of this study was to determine the effectiveness of infusion of ginger and mint leaves in reducing the frequency of nausea and vomiting in pregnant women in the first trimester at Batua Health Center Makassar. This research method is a quasi-experimental research with a pre- and post-test design approach without a control group. This research uses a purposive sampling technique. The statistical test used is Paired Sample t. Test to determine nausea and vomiting before and after the intervention of ginger and mint leaves and T. Independent test to determine nausea and vomiting in the group given ginger and mint leaves. Based on the results using Paired Sample t. The test shows the value of P = 0.000 with a significant level of = 0.05. Therefore, the P value = <0.05, which means that Ho is accepted and Ha is rejected, which means that there is a decrease in the frequency of nausea and vomiting in the administration of boiled ginger and mint leaves. With the Independent T test, it was found that the value of P < then the administration of ginger steeping was very effective in reducing the frequency of nausea and vomitingin First Trimester pregnant women.